2013
DOI: 10.1097/tp.0b013e3182754c53
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Derived Mesenchymal Stem Cells Combined With Low-Dose Tacrolimus Prevent Acute Rejection After Renal Transplantation

Abstract: These preliminary data suggest that the use of MSCs could provide potential benefits in renal transplantation by reducing the dosage of conventional immunosuppressive drug that is required to maintain long-term graft survival and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
116
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 32 publications
4
116
0
6
Order By: Relevance
“…Furthermore, MSCs combined with cyclosporine A (CsA) induced tolerance of islet allografts in immune-deficient mice [14]. In a kidney allograft model, MSCs led to long-term graft acceptance in rodents [19] and had immunosuppressive effects in renal transplant recipients [22][23][24], which suggested that MSCs may reduce immunosuppressant dosage [25,26]. Collectively, these studies suggested that under certain conditions, MSCs could prolong allograft survival in combination with clinical immunosuppressants.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, MSCs combined with cyclosporine A (CsA) induced tolerance of islet allografts in immune-deficient mice [14]. In a kidney allograft model, MSCs led to long-term graft acceptance in rodents [19] and had immunosuppressive effects in renal transplant recipients [22][23][24], which suggested that MSCs may reduce immunosuppressant dosage [25,26]. Collectively, these studies suggested that under certain conditions, MSCs could prolong allograft survival in combination with clinical immunosuppressants.…”
Section: Introductionmentioning
confidence: 88%
“…The authors of this study concluded that autologous mesenchymal stem cell injection results in a lower incidence of acute rejection, a decreased risk of opportunistic infection and better regulated renal function at 1 year. Thus, although these studies differ in many aspects, such as the type of mesenchymal stem cells, their allogeneic or autologous status, their time and site of injection and protocols of immunosuppressive therapy, all of them suggest that stem cell injection is a safe strategy [90][91][92][93][94]. However, these studies were performed in LD kidneys, and not in those obtained through DBD or DCD, which are more sensitive to ischemia-reperfusion sequence.…”
Section: Strategies To Limit Renal Ischemia-reperfusion Injuries Andmentioning
confidence: 99%
“…The results of this showed no toxic adverse effects associated with MSC infusion and all patients survived with stable graft function to 12 mo with only 1 acute rejection episode in the control group. The one difference they did notice was elevated B-cell counts in the MSC group at 3 mo compared to the control [58] . They concluded that MSCs may provide benefits in renal transplantation by reducing the required dose of conventional immunosuppressive drug that is required for long term graft survival.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…They concluded that pre-transplant administration of MSCs avoided the cell induced graft dysfunction associated with posttransplant MSC administration and that this method is favourable for future trials. Peng et al [58] examined the effect of autologous MSCs on renal transplants by giving 6 patients MSCs combined with half doses of tacrolimus and comparing acute rejection, graft function, and graft survival at 12 mo to a control group of 6 patients receiving standard dose tacrolimus. The results of this showed no toxic adverse effects associated with MSC infusion and all patients survived with stable graft function to 12 mo with only 1 acute rejection episode in the control group.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%